Highly effective frontal stunning procedure using a pneumatic penetrating captive bolt in water buffaloes - Molnar Fernández, Valeria (2023)
An effective frontal stunning procedure in water buffaloes was assessed using a pneumatic penetrating captive bolt (PPCB) with high air pressure. The study contemplated two phases; first, 352 buffaloes and 168 post-mortem heads were evaluated to determine the most effective anatomical site for stunning. Then, the second phase (n = 182) was used to validate the stunning procedure at the discovered anatomical site in the first phase, which was located 8 cm dorsal above the middle of the forehead on an "X" formed between the eyes and the base of the contralateral horns, and 2 cm lateral, avoiding the midline, where the skull tended to narrow. A total of 95.1% of buffaloes received effective stunning at the first shot with evidence of the presence of collapse, absence of rhythmic breathing, and absence of ocular reflexes (corneal and palpebral). There were no differences in the stunning efficacy by sex, breed, or skull thickness. These findings demonstrated that stunning with a PPCB at pressures of 1379-1516.8 KPa (200-220 pounds per square inch (psi)) in the site reported here produces a highly effective stunning at the first shot in water buffaloes.